Mudharabah Compliance Analysis of Potato-Farming Capital Schemes: A Qualitative Case Study of Smallholder–Patron Relations in Cikembang Village, Bandung Regency, West Java - Ashidiq, Yusron Hasbi (Institut Agama Islam Persis Bandung, 2026)
Smallholder farmers in rural Indonesia frequently rely on informal capital arrangements with wealthier patron-traders, yet whether these arrangements conform to Islamic profit-sharing principles particularly mudharabah has received limited empirical scrutiny. This study examines the existing capital scheme that mediates the relationship between large and small potato farmers in Cikembang Village, Kertasari District, Bandung Regency, West Java, and evaluates its compliance with the substantive provisions of mudharabah in Islamic economics. A qualitative case-study design was employed, with primary data drawn from semi-structured interviews with five purposively selected informants comprising one patron-financier and four smallholder borrowers, supplemented by participant observation and document analysis of village administrative records. Data were analysed using thematic analysis with a deductive framework derived from the rukn (pillars) and shurut (conditions) of mudharabah. The findings reveal that the prevailing capital scheme operates through a four-stage informal cycle oral agreement, capital disbursement without collateral, post-harvest repayment via crop delivery, and below-market price deduction which has functioned for over a decade as a community norm. While the scheme provides accessible financing without bank-style procedural barriers, three substantive divergences from mudharabah are identified: (1) the absence of a written contract specifying profit-sharing ratio (nisbah) introduces gharar; (2) the obligation to sell harvest output exclusively to the financier at below-market prices constitutes an exploitative element inconsistent with the freedom-of-trade principle; and (3) the asymmetric loss-bearing arrangement, in which crop failure is borne entirely by the smallholder, contradicts the mudharabah principle that financial loss falls on the capital provider (shahibul maal). The study contributes to the literature on the operationalisation of Islamic finance principles in rural informal economies and recommends a reformed scheme based on written mudharabah contracts, transparent market-based pricing, and shared loss-bearing to align Cikembang's capital practices with Sharia provisions.